Description of a new species of the Afrotropical spider genus Afroneutria (Araneae, Ctenidae) - Polotow, Daniele; Jocqué, Rudy (Zootaxa, 2016)
A species of the Afrotropical spider genus Afroneutria is newly described. Afroneutria tanga sp. nov is endemic to Tanzania, southeast Africa, and can be distinguished from the remaining species of the genus by the retrolateral excavation of the embolus. An identification key for all Afroneutria species is presented.